Comparação dos resultados entre biópsia de congelação e análise anatomopatológica em mulheres submetidas a tratamento cirúrgico de lesões de ovário - Lima, Karine Kelly Frausino [UNESP] (2024)
Purpose: To compare the concordance index between the results of the intraoperative frozen section biopsy and the final histopathological study in patients undergoing surgical treatment for adnexal lesions at a public university referral service. Patients and Methods: This was a retrospective, single-center cross-sectional study with analysis of computerized medical records of patients who underwent surgical treatment of ovarian lesions between January 2017 and January 2022. Epidemiological characteristics, preoperative imaging tests, tumor markers, and intraoperative biopsy and histopathological analysis were evaluated. The study of the agreement between frozen section and histopathological tests was performed using the Weighted Kappa coefficient. The other variables were statistically analyzed using the Student's t-test, the Mann-Whitney test, and the Goodman association test. Results: A total of 528 women were identified in the institution's registration system, 349 of whom were excluded because they did not meet the inclusion criteria. Thus, 179 patients were included and 62 underwent frozen section testing, the others were accepted as intraoperative macroscopes, and were submitted only to histopathological testing. The agreement rate between the frozen section test and the final histopathological evaluation was 80.6%, and a strong association was considered with the Weighted Kappa value Kw=0.713. Young women with a BMI > 30 showed a greater tendency for disagreements between the two analyses. Risk stratification using O-RADS showed a higher proportion of agreement in lesions classified as O-RADS 4 and, despite its non-specificity, CA125 remains the main preoperative marker of suspicious adnexal masses, and these findings were all statistically significant (P<0.05). Conclusion: In general, women diagnosed with suspicious adnexal masses benefit from intraoperative frozen section biopsy, and the diagnostic hypothesis based on clinical, laboratory, and imaging evaluation demonstrated a significant correlation with the findings of both the frozen section examination and the histopathological study. One of the justifications for a lower concordance rate observed in our study, observed in our study, may be the fact of the reduced number of requests in our service, even so, the statistical analysis showed a strong agreement between the results of the two evaluations, which justifies additional studies with a larger number of patients to improve the experience of our service.